Analysis of Physical and Non-Physical Potential of Bereng Berkawat Village, Beduai Subdistrict, Sanggau Regency - Daniel, Sofian; Anasi, Putri Tipa; Rahmadania, Anissa Hayfa Dwi; Sansan, Anggela; Melani, Hesty; Christanto, Ludovicus Manditya Hari (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This article aims to identify the physical and non-physical potential of various aspects such as economy, socio-culture, health, education, settlement, and government, as well as to identify factors that support village progress and to understand the classification of Bereng Berkawat Village. This research uses a descriptive qualitative method with data collection through documentation, interviews, and direct observation. The village has a majority Malay population, followed by Dayak and Javanese, with around 80% of the population being Muslim. Cultural life is still preserved with traditional arts such as jipin and Dayak dances. It has a clustered service center pattern. Health and education facilities are available, including a health center and elementary school. Small and medium enterprises, such as grocery stores, serve as centers of economic and social interaction. The high enthusiasm of the community and the support of the government are the main keys to the sustainable development of this village. Based on the results of the study, Bereng Berkawat Village is classified as a self-sufficient village because it has begun to experience outside influences, more advanced technology, better infrastructure, and more diverse livelihood.